Preparation and Characterization of Imprinted Polymers Based on Cobalt(II)-Enrofloxacin Coordination - Lv, Yun-Kai; Zhang, Qian; Song, Yan-Ling; Yan, Shuai-Lei (Asian Journal of Chemistry, 2011)
Molecularly imprinted polymers of enrofloxacin were investigated firstly with 4-vinylpyridine as functional monomer which based on cobalt(II)-enrofloxacin coordination. The results of equilibrium binding experiments show that the molecularly imprinted polymers had higher binding capacity for enrofloxacin than the control imprinted polymer prepared using the same method but in the absence of both cobalt(II) and enrofloxacin or cobalt(II) ion. The influences of metal ions and pH of solution on the recognition performance of the molecularly imprinted polymers were investigated in protic solvent. Scatchard analysis show that two classes of binding sites existed in the metal complex imprinted polymers, with their maximum apparent binding capacity estimated to be 102.76 μmol g-1 and 65.23 μmol g-1, respectively. The results on substrate selectivity of imprinted polymer revealed that the molecularly imprinted polymers had better binding affinity for template among the tested compounds. This type of molecularly imprinted polymers could be prepared in protic solvent because of the relative strong interaction between the template complex and the functional monomer.